Design and analysis of closed-loop supply chain networks - Pazhani, Subramanian (Boca Raton : CRC Press/Taylor & Francis Group, 2021)
"Closed-Loop Supply Chains and its management have become mandatory to stay competitive and profitable, with product return values skyrocketing for a single retailer. This book provides insights for designing supply chain networks by understanding and incorporating key return parameters into their design, which will affect profitability. Integrated forward and reverse supply chain is analyzed with a focus on refurbishing networks with commercial returns. The quality of returned products is incorporated into the network design framework and is a key parameter in deciding optimal discounts on the refurbished products. The book will discuss how customer categories and their acceptance behavior is incorporated into the network design. The book will also show how to analysis the interaction of parameters on supply chain network design and profitability, offers modeling framework for uncertainties in the return product parameters, and how to design a robust network. This book will be invaluable for managers in designing a sustainable, robust, and profitable supply chain network. Ideal for managers, practitioners, and researchers in the area of supply chain network design and optimization"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics; BUSINESS & ECONOMICS / Purchasing & Buying; TECHNOLOGY / Manufacturing; BUSINESS & ECONOMICS / Industries / Manufacturing Industries